Pertumbuhan Maggot Hermetia illucens L. pada Media Kombinasi Bungkil Kelapa Sawit yang Difermentasi dan Dedak Padi - Yanti, Ari Hepi; Rahmanisya, Afifah; Saputra, Firman (Life Science, 2024)
Maggot Hermetia illucens is the larval phase of the black soldier fly. This study aims to analyze the development of maggots in the form of length, body weight and population density in a combination of fermented oil palm meal and rice bran. The study used a Complete Randomized Design (RAL) with 5 treatments and 5 repeats for 21 days, namely 100% oil palm meal, 75% oil palm meal and 25% rice bran, 50% oil palm meal and 50% rice bran, 25% oil palm meal and 75% rice bran, and 100% rice bran. Random sampling is used for data collection. The length of the maggot's body is measured using a digital caliper. The total weight of the maggots on each treatment on the 21st day was weighed for weight measurement. Density is measured by counting the number of individuals per volume of media. Data were analyzed with single-track ANOVA and Tukey test. The results showed significant growth of Hermetia illucens maggots (p = 0.000) using a combination of fermented oil palm meal media and rice bran. The combination of 75% oil palm meal and 25% rice bran has a significant effect with the highest length for 21 days at 27.56 mm, a total weight of 34.86 grams. Its population density is insignificant.